TI_GERICHTE 52.2017.212 vom 14. März 2017 , Ordine di messa fuori servizio delle serpentine nella lavanderia e nel locale tecnico - TI Tribunale d'appello (2017)
Ordine di messa fuori servizio delle serpentine nella lavanderia e nel locale tecnico